Alcohol outlet density and adolescent drinking behaviors in Thailand, 2007-2017: A spatiotemporal mixed model analysis. - Polathep Vichitkunakorn; Sawitri Assanangkornchai; Kanittha Thaikla; Suhaimee Buya; Supeecha Rungruang; Mfahmee Talib; Warangkhana Duangpaen; Warintorn Bunyanukul; Monsicha Sittisombut (PLoS ONE)
This study aimed to explore the relationship between alcohol outlet density and the proportion of alcohol consumption among Thai adolescents. We utilized the alcohol consumption data from the 2007, 2011, and 2017 Tobacco and Alcohol Consumption Survey in Thailand. We analyzed the relationships between alcohol sales license figures and consumption behavior using a spatiotemporal mixed model. Our data had two levels. The upper (provincial) level featured alcohol sales license density (spatial effect), the years of survey (temporal effect), and the social deprivation index. The lower (individual) level included the demographic data of the adolescents. A total of 9,566 Thai adolescents participated in this study, based on surveys conducted in 2007 (n = 4,731), 2011 (n = 3,466), and 2017 (n = 1,369). The density of alcohol sales licenses increased the odds for the one-year current drinker category (odds ratio [OR] = 1.08, 95% confidence interval [CI], 1.04-1.45), especially in male adolescents (OR = 1.09, 95% CI, 1.04-1.14). Furthermore, it increased the odds for the heavy episodic drinker category for female adolescents (OR = 1.23, 95% CI, 1.05-1.44). Increased alcohol sales licenses are associated with higher alcohol consumption among Thai adolescents. This highlights the need for government organizations to develop and apply strategies to reduce the number of licenses for the sale of alcohol.